Functions of stationary industrial meetings in 1970’s (case study of Kalmykia) - Sartikova, Evgenia V. (The New Research of Tuva, 2015)
Article describes the activities of stationary industrial meetings in 1970’s in the Republic of Kalmykia. Source basis for the article is the National Archives of the Republic of Kalmykia. Analysis of a wide range of sources revealed that as a result of stationary industrial meetings Kalmyk trade unions contributed much to the development of republican economy. But the real influence of trade unions to engaging the workers to managing of industry had been poor.